Intercultural Communication in Second/Foreign Language Education Over 67 Years: A Bibliometric Review - Ngô, Công Lem (Taylor and Francis, 2025)
This bibliometric review analyzed 2,429 publications on intercultural communication in second/foreign language education from Scopus over 67 years. Findings highlight the growing integration of intercultural competence (IC) into curricula, with digital tools like telecollaboration and e-learning playing significant roles. Keywords such as “intercultural competence,” “students,” and “teaching” underscore IC’s pivotal role in shaping pedagogical strategies. The USA and China lead research output, while emerging trends include gender dynamics and technology-mediated learning. These findings stress the need for professional development, culturally responsive materials, and IC-focused learning outcomes in language education.